COMPOSITE CIRCUIT AIRCRAFT WITH AIR-CUSHION CHASSIS PITCHING MOMENT CONTROL - Yu. Yu. Merzlikin; A. A. Dolgopolov; V. G. Cipenko (Научный вестник МГТУ ГА)
Efficiency of air-cushion chassis pitching moment control by nozzles rotation at take-off and landing condition of aircraft experimental research is carried out. Researches were conducted using double circuit air-cushion vehicle nozzle device with rotary sheets-nozzles at “flat cell” test bench. During the experiment parameters, such as: incident flow speed V, pressure at receiver Pp, height of model above the plane h, angle of pitch υ, nozzle mounting angles QUOTE , QUOTE were varied.